Dampak Perubahan Iklim Terhadap Konflik Sosial Dan Kekerasan Gender: Studi Kasus Keamanan Manusia Di Sub Sahara Afrika - Sitorus, Lydia Angelica; Santoso, Made Panji Teguh; Marsingga, Prilla (Jurnal Ilmiah Wahana Pendidikan, 2025)
Climate change is a global issue that has major impacts, especially in Sub-Saharan Africa. The increasingly frequent occurrence of extreme weather phenomena such as droughts, floods and heat waves has led to social and economic insecurity, which can lead to social conflict and gender-based violence. In these situations, climate change increases competition over natural resources, intensifies conflicts between communities, and encourages forced migration. Vulnerable groups, such as women, who are often victims of conflict, feel these impacts most acutely. This study uses a human security approach to analyze the impact of climate change on social conflict and gender violence in Sub-Saharan Africa. The research aims to illustrate how climate change exacerbates societal vulnerabilities and fuels conflict dynamics in the area. This research uses descriptive qualitative methods and secondary data.